Strategi Pengembangan Ternak Kerbau Di Kabupaten Manggarai Barat - Rustam Ahmad; Maria Yusintha Luruk; Ulrikus R Lole (Jurusan Agribisnis Fakultas Pertanian Universitas Sultan Ageng Tirtayasa, 2020)
Buffalo has a huge role in community life in West Manggarai Regency, both as working and as socio-cultural livestock such as for deaths and marriages. However, government support in the development of buffalo is meager, increasing buffalo population fluctuations. This condition exacerbated by the availability of males and buffalo breeding patterns is still traditional. This study aims to formulate priority strategies and programs in the context of buffalo development. This study uses the SWOT and AHP methods to formulate strategy and determine priority strategies and programs. This study uses survey methods, and sampling by purposive sampling with criteria for the number of buffalo livestock ownership of at least five has sold buffalo in the last three years and has a productive female. Through the results of the SWOT and AHP analysis strategies in the development of buffalo in Manggarai Barat District, increasing buffalo production and productivity are top priorities, improving human resource skills and institutional strengthening of second priority farms, optimizing the availability of pasture fields and third-priority agricultural waste, and increasing synergy fourth priority supporting institutions. Priority programs in the context of developing buffalo are strengthening institutional livestock with a weight of 0.1481, improving human resource skills with a load of 0.1410, providing a superior male program with a weight of 0.1376, mapping and revitalization of pasture fields with a weight of 0.1256, supplying animal feed with a load of 0.1069, applying processing technology feed with a weight of 0.0951, increased use of financial institutions with a weight of 0.0705, prevention and control of ruminant livestock diseases with a load of 0.0651, increase the synergy of the world of high poaching with the world of animal husbandry with a weight of 0.0585, construction of supporting facilities and infrastructure with a load of 0.0469. The Government of West Manggarai Regency expected to schedule synergistically as well as implement it; so that the buffalo development policy is right on target and can increase the buffalo population so that it will lead to the progress and improvement of the welfare of buffalo ranchers.